ATURAN PAKAIAN UNTUK MENGHADIRI BARALEK PERKAWINAN BAGI WANITA DI KENAGARIAN VII KOTO TALAGO KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Efriani, Rimelda; Nazar, Ernawati; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of research is describethe rule, shape and meaning of clothing philosophy attended the wedding event for woman in Kenagarian VII Koto Talago Kecamatan Guguak Kabupaten Lima Puluh Kota. This study is a descriptive kualitatif study. Object this study is rule, shape and meaning of clothing philosophy attended the wedding event for woman in Kenagarian VII Koto Talago Kecamatan Guguak Kabupaten Lima Puluh Kota. Data collection techniques with observation, interview and documentation. Analysis techniques with reduction data, display of data and conclusion. The results showed that rules about attending marriage attire have written rules socialized, clothing used by Bundo Kanduang used kuruang basiba clotch, tingkuluak kompong, salempang, saruang2jao and slipper which is closed on the front. The meaning of philosophy contained in kuruang basiba clotch is women must be careful field, not selfish, can accept input from others, open and willing to associate with anyone. Tingkuluak kompong has a meaning, minang women are people who are customary and religious. The sling describes Bundo Kanduang as having a great responsibility towards her husband and child. Sarung batik with a cloth head placed on the back contains meaning, wherever he goes should always remember the child and her husband waiting at home. Slipper that are closed on the front of the model means that the wearing can keep a secret .Keywords : Wedding, Baju Kuruang, in Kenagarian VII Koto Talago